Ritual matters : material residues of ancient religions - Knust, Jennifer Wright, 1966-; Moser, Claudia (Memoirs of the American Academy in Rome. Supplementary volume ;, 2017)
"Ritual Matters interrupts the anachronistic binaries of religious practice and belief, the material and the theological, by taking a new approach to the study of archaeological remains of ancient religions. Focusing on the materiality of ritual--inherent in everything from monumental temples and altars, to votive offerings and codices, to sanctioned inscriptions and reliefs--allows for a novel vantage point from which to consider ancient religious practices, as well as an important counterbalance to more traditional conceptual perspectives often privileged in the field ... Topics covered include funerary remains, sacrificial practices, "magic," Roman altars, imperial reliefs and statuary, and the role of sacred books"--Publisher